Cover Image. (June 2018) - Du, Guangyan; Fu, Lingling; Jia, Jun; Pang, Xu; Yu, Haiyang; Zhang, Youcai; Fan, Guanwei; Gao, Xiumei; Han, Lifeng
Abstract : The cover image, by Guangyan Du et al., is based on the Research Article Validated UPLC‐MS/MS method for quantification of seven compounds in rat plasma and tissues: Application to pharmacokinetic and tissue distribution studies in rats after oral administration of extract of Eclipta prostrata L., https://doi.org/10.1002/bmc.4191 .